EFFORTS TO PREVENT TRAFFIC VIOLATON THROUGH THE TRAFFIC COMMUNITY EDUCATION PROGRAM BY THE TEMANGGUNG RESOR POLICE TRAFFIC UNIT - andhika pratistha (Indonesian Journal of Police Studies, 2022)
The background of writing this final project is the large number of traffic violations in the Temanggung Regency area. By using a descriptive method, the Temanggung Police Traffic Unit makes efforts to prevent traffic violations through the Traffic Community Education program so it can create a secure, safe, and dicipline community. The purpose of this paper is to determine the efforts and application in preventing traffic violations through the Traffic Community Education program by Temanggung Police Traffic Unit. As a basic analysis, the author uses several concepts and theories, which is: the concept of traffic, the concept of violation, the concept of traffic violations, the concept of Traffic Community Education Program, communication theory, and management theory. With the research area in the Police Station Temanggung Regency area. This research was conducted with an qualitative approach, using the type of field research, as well as data collection techniques in the form of interviews, observations, and document studies. The location of the research conducted by the author is in Temanggung Regency area. It was found that there were several obstacles in the results of the education application through the Traffic Community Education program, which is planning, organizing, actuating and controlling stages. Several obstacles were also found in efforts and application in preventing traffic violations through the Traffic Community Education program by the Satlantas Police Temanggung, such as the limited quantity and quality of members numbers, as well as activity plans that were not in accordance with the stated objectives.